Section 6: Education and Consumer Informatics: The Path towards eHealth: Obstacles along the Way - Jadad, A. R.; Enkin, M. W. (Yearbook of Medical Informatics, 2006)
The two authors of this article share both a strong interest in, and deep concerns about, the use of eHealth (electronic information and communication technologies for improving or maintaining health). In this article, we identify some unanticipated obstacles to effective use of eHealth.We reflected upon the potential of information and communication technologies to transform the health system and its failure to achieve that potential.We chose seven obstacles: the insufficient emphasis on health in eHealth, the lack of time for reflection, the development of a fortress mentality, poor evaluation of efforts, lack of involvement of youth, inequity, and a parochial attitude that precludes economies of scale. Whenever possible, we provided examples of innovative initiatives that illustrate potential ways to meet our current challenges.We believe that the obstacles we describe in this article can be overcome. The impediments are not only technological, but also cognitive, financial and political. To succeed will require a major shift from our ethic of competition to one of generosity, commitment, and collaboration; enlightened, as opposed to narrow, self-interest.
Keywords: e-health